2016
DOI: 10.1161/atvbaha.115.306397
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Periostin Protects Against Atherosclerosis in Mice by Altering Inflammation and Extracellular Matrix Remodeling

Abstract: Objective Periostin is a secreted protein that can alter extracellular matrix remodeling in response to tissue injury. However, the functional role of periostin in the development of atherosclerotic plaques has yet to be described despite its observed induction in diseased vessels and presence in the serum. Approach and Results Hyperlipidemic, apolipoprotein E-null mice (ApoE−/−) were crossed with periostin (Postn−/−) gene-deleted mice and placed on a high fat diet for 6 or 14 weeks to induce atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…Recent evidence points to an important role of components of the ECM from both a biomarker and a therapeutic prospective in PAH . The most upregulated gene in severe PAH was indeed periostin, another matricellular protein involved in response to vascular injury and regulation of SMC proliferation . Chronic normobaric hypoxic exposure for 2 weeks significantly increased the mRNA level of periostin in the rat lung and hypoxia‐induced periostin expression was localized to PA‐SMC of hypertrophic PA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence points to an important role of components of the ECM from both a biomarker and a therapeutic prospective in PAH . The most upregulated gene in severe PAH was indeed periostin, another matricellular protein involved in response to vascular injury and regulation of SMC proliferation . Chronic normobaric hypoxic exposure for 2 weeks significantly increased the mRNA level of periostin in the rat lung and hypoxia‐induced periostin expression was localized to PA‐SMC of hypertrophic PA.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the exact role of this protein in allergic patients, it has been described as a marker for asthma severity and been associated with epithelial remodeling processes in airway mucosa. [15][16][17]34 Regarding immunologic characteristics, allergic patients had a progressive inflammatory profile. Although allergic responses in the gut and lung mucosa have been investigated, 35 allergic inflammation in the oral mucosa remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Schwanekamp et al examined the role of periostin, a secreted ECM protein, on the development of atherosclerosis in an ApoE−/− model. 67 These authors found that periostin-deficient, ApoE-null mice developed reduced plaque areas, fewer plaque macrophages, disorganized plaque ECM, thinner fibrotic caps, and increased MMP-2 and MMP-13 levels than ApoE-null control mice. 67 It would be interesting to determine if the reduced number of plaque macrophages observed in the absence of periostin was the result of reduced plaque SMC transition to a macrophage-like phenotype now that the necessary mouse genetic tools are available to test this possibility.…”
Section: Vascular Smcs Inflammation and Atherosclerosismentioning
confidence: 96%